1980
DOI: 10.1111/j.1600-0447.1980.tb00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte subpopulations in peripheral blood from schizophrenic patients

Abstract: Patients with acute and chronic schizophrenia were examined for T and Fc receptor-bearing lymphocytes in blood by means of rosette techniques. The patients had normal numbers of peripheral blood lymphocytes. The percentage of T lymphocytes in patients with acute schizophrenia was reduced (60 +/-2%) compared with controls (66 +/- 1%) and patients with chronic schizophrenia (67 +/- 3%). The total number of T lymphocytes was significantly decreased in patients with acute schizophrenia had slightly elevated number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…A role of T cells in schizophrenia though was first indicated more than 35 years ago (Nyland et al 1980), the macrophage-T lymphocyte theory of schizophrenia was proposed in 1992 and this was further supported in 1995 (Smith 1992;Smith and Maes 1995). Subsequent to this, many studies consistently demonstrated aberrant Tcell mediated immunity in schizophrenia (Table 1).…”
Section: T Cell Theory Of Schizophrenia Revisitedmentioning
confidence: 94%
“…A role of T cells in schizophrenia though was first indicated more than 35 years ago (Nyland et al 1980), the macrophage-T lymphocyte theory of schizophrenia was proposed in 1992 and this was further supported in 1995 (Smith 1992;Smith and Maes 1995). Subsequent to this, many studies consistently demonstrated aberrant Tcell mediated immunity in schizophrenia (Table 1).…”
Section: T Cell Theory Of Schizophrenia Revisitedmentioning
confidence: 94%
“…= 6.3, range [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In order to rule out the possibility of a schizophreniform disorder, patients in the present study were chosen if they had at least one previous hospitalization.…”
Section: Methods and Subjectsmentioning
confidence: 99%
“…On the cellular level, a decrease in the reactivity of lymphocytes [47][48] and the presence of large morphologically abnormal lymphocytes [47] were reported. A decrease in the percentage of T cells in schizophrenic patients with a severe recurrence was also observed [49] , whereas in untreated patients an increase in T suppressor lymphocytes was noted [50] . In addition, an increase in the ratio of T helper cells to T suppressor cells was found to correlate with the patients' psychiatric condition [51] .…”
Section: Discussionmentioning
confidence: 99%